Swearing in comment section: Investigating netizens’ involvement in virtual political arena - Teguh Setiawan; Suhardi Suhardi; Beniati Lestyarini (Indonesian Journal of Applied Linguistics)
Swearing is a verbal behavior that uses profanity and taboo words to express emotions and anger and exists in every language and culture. Despite its notorious use as language expressions, swearing actually function to indicate the user’s degree of involvement in certain communicative event. This study observed the use of language in digitally-mediated communication setting. The aim of the present study is to investigate netizen’s involvement in a political discourse, as reflected in the use of their language in the comment sections of online political news. Using a combination of transitivity analysis (Eggins, 2004) and the use of swearing (Eggins and Slade, 1997), the study investigated functions of swearing and the role of swear-words users in political commenting discourse. The study identified the most frequently used swear-words are taboo words, which are targeted to the reported person and opposing parties to the incumbent government. This further indicates how the netizens are split into two groups namely supporters and opponents of certain political figures or parties.